Emipy: An open-source Python-based tool to analyze industrial emissions in Europe - Florian A. Overberg; Philipp C. Böttcher; Dirk Witthaut; Simon Morgenthaler (SoftwareX, 2023)
Targeted information about carbon dioxide emissions and various other pollutants is essential for research and consulting in environmental protection, public health and energy systems analysis. The European Pollutant Release and Transfer Register (E-PRTR) provides an extensive database of emissions in the European Union, covering approximately 100 substances at facility level. Emipy is a Python package specifically written to access, manipulate, analyze and visualize the data provided by the E-PRTR. It manages several pre-processing steps, including fully-automated data download and merging. Emipy includes several built-in filter and visualization functions and thus enables quick access to the E-PRTR. Since emipy utilizes common Python packages and classes such as pandas and matplotlib, it can easily be integrated into other software tools. Using the built-in export functions for the popular modeling framework Calliope, emipy is particularly suited for use in energy system modeling.